International Covenant on the Right to Development : Implications for Developing Countries and the Global Balance of Power - Ngang, Carol Chi (Social Sciences E-Books Online, Collection 2026., 2025)
In this pioneer compilation of academic literature on the International Covenant on the Right to Development, including some of the leading experts on the subject, the authors delve at length into the central enquiry on how and to what extent the Covenant will, as a binding instrument of international law, shape the global balance of power. Envisaged to be incorporated in the international bill of human rights, the analysis on the various component elements leads to the conclusive argument that, once in force, the Covenant on the Right to Development will have major implications for how the international order is structured and how development is henceforth pursued.